Regulatory RNAs discovered in unexpected places. (1st October 2015) - Pek, Jun Wei; Okamura, Katsutomo
Abstract : Recent studies have discovered both small and long noncoding RNAs (ncRNAs) encoded in unexpected places. These ncRNA genes were surprises at the time of their discovery, but many quickly became well‐accepted families of functional regulatory RNA species. Even after years of extensive gene annotation studies using high‐throughput sequencing technologies, new types of ncRNA genes continue to be discovered in unexpected places. We highlight ncRNAs that have atypical structures and that are encoded in what are generally considered 'junk' sequences, such as spacers and introns. We also discuss current bottlenecks in the approaches for identifying novel ncRNAs and the possibility that many remain to be discovered. WIREs RNA 2015, 6:671–686. doi: 10.1002/wrna.1309 This article is categorized under: RNA Evolution and Genomics > Computational Analyses of RNA RNA Turnover and Surveillance > Regulation of RNA Stability Regulatory RNAs/RNAi/Riboswitches > Regulatory RNAs